THE RECOGNITION OF A DIARYLIMINE AS A METABONATE PRODUCED DURING INCUBATION OF N-BENZYL-4-CHLOROANILINE WITH HEPATIC-MICROSOMAL PREPARATIONS - (:unkn) unknown (ROYAL PHARMACEUTICAL SOC GREAT BRITAIN, 1994)
Evidence is presented for the formation of N-benzylidene-4-chloroaniline as a metabonate during the metabolism of N-benzyl-4-chloroaniline. Control studies suggest that the diarylimine is formed as a chemical artifact from the debenzylation products (benzaldehyde and 4-chloroaniline). This novel observation indicates a possible pathway to amide formation from N-benzylanilines via diarylimines as intermediates.
Keywords: N-OXIDATION; C-OXIDATION; METABOLISM